2014
DOI: 10.1891/1946-6560.5.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Abuse and Women’s Use of Intimate Partner Violence: Exploring the Role of Complex Trauma

Abstract: Much research now indicates significant long-term effects for individuals who have experienced various forms of abuse in childhood. Recent research also has examined the role of women as perpetrators of intimate partner violence (IPV), including potential factors that contribute to their use of violence. One trend revealed in the research is that many of the women who engaged in acts of IPV also had a history of experiencing one or more types of childhood abuse (e.g., physical or sexual abuse, or witnessing fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The extant literature on IPV, as well as clinical best practices, suggest that childhood abuse and neglect (CAN), including childhood physical, sexual, and emotional abuse; exposure to domestic violence (DV); and exposure to emotional and physical neglect, is a key risk factor for perpetration of IPV as an adult. Some research demonstrates a direct relationship between CAN and adult IPV, particularly for female perpetrators of IPV (e.g., Fang & Corso, 2008; Flemke, Underwood, & Allen, 2014; Trabold, Swogger, Walsh, & Cerulli, 2015) and survivors of childhood sexual abuse (e.g., Fang & Corso, 2008; Jennings, Richards, Tomsich, & Gover, 2015; McMahon et al, 2015; Teitelman et al, 2017). Other research proposes mediators or moderators between CAN and IPV perpetration such as emotion dysregulation (Gratz, Paulson, Jakupcak, & Tull, 2009), anger expression and stress reactivity (Maneta, Cohen, Schulz, & Waldinger, 2012), a hostile-dominant interpersonal style (Edwards, Dixon, Gidycz, & Desai, 2014; Murphy & Blumenthal, 2000), attachment anxiety (Brassard, Darveau, Péloquin, Lussier, & Shaver, 2014), and psychopathic traits (Swogger, Walsh, Kosson, Cashman-Brown, & Caine, 2012).…”
mentioning
confidence: 99%
“…The extant literature on IPV, as well as clinical best practices, suggest that childhood abuse and neglect (CAN), including childhood physical, sexual, and emotional abuse; exposure to domestic violence (DV); and exposure to emotional and physical neglect, is a key risk factor for perpetration of IPV as an adult. Some research demonstrates a direct relationship between CAN and adult IPV, particularly for female perpetrators of IPV (e.g., Fang & Corso, 2008; Flemke, Underwood, & Allen, 2014; Trabold, Swogger, Walsh, & Cerulli, 2015) and survivors of childhood sexual abuse (e.g., Fang & Corso, 2008; Jennings, Richards, Tomsich, & Gover, 2015; McMahon et al, 2015; Teitelman et al, 2017). Other research proposes mediators or moderators between CAN and IPV perpetration such as emotion dysregulation (Gratz, Paulson, Jakupcak, & Tull, 2009), anger expression and stress reactivity (Maneta, Cohen, Schulz, & Waldinger, 2012), a hostile-dominant interpersonal style (Edwards, Dixon, Gidycz, & Desai, 2014; Murphy & Blumenthal, 2000), attachment anxiety (Brassard, Darveau, Péloquin, Lussier, & Shaver, 2014), and psychopathic traits (Swogger, Walsh, Kosson, Cashman-Brown, & Caine, 2012).…”
mentioning
confidence: 99%
“…One way to develop understanding of this phenomenon is to explore the childhood experiences of women involved in such violence. Research on female family‐violence and childhood experiences has focused primarily on women who have been convicted of family‐violence and received court‐ordered help . There are several batterer intervention programs developed for men aiming to reduce men's power and controlling behavior against women, but it has been suggested that family‐of‐origin issues are essential to consider when designing interventions for female family‐violence perpetrators .…”
mentioning
confidence: 99%
“…Research on female family-violence and childhood experiences has focused primarily on women who have been convicted of family-violence and received court-ordered help. [3][4][5] There are several batterer intervention programs developed for men aiming to reduce men's power and controlling behavior against women, 6 but it has been suggested that family-of-origin issues are essential to consider when designing interventions for female family-violence perpetrators. 7 The purpose of this study was to explore childhood experiences of female family-violence perpetrators who voluntarily sought help.…”
mentioning
confidence: 99%
“…IPV occurs in both heterosexual and homosexual relationships and does not require sexual intimacy (CDC, 2015). IPV can be unidirectional, meaning only one partner is the abuser, or bidirectional (also referred to as mutual or reciprocal IPV) in which both partners are abusive toward each other (Flemke & Underwood, 2014;Gay et al, 2013;Iverson et al, 2014).…”
Section: Intimate Partner Violencementioning
confidence: 99%
“…A study of American college women indicated that emotional CM had a stronger link to all forms of IPV than any other type of CM (Gay et al, 2013), while another study conducted with both men and women demonstrated that neglect had the most significant link to IPV (Widom et al, 2014). Other researchers have found that more severe IPV is linked to specific forms of CM: betrayal trauma (CM perpetrated by a trusted primary caregiver on which the child is dependent for survival, usually a parent) (Babcock & DePrince, 2012;Babcock & DePrince, 2013), complex trauma (repeated and sustained CM perpetrated by a primary caregiver at key, early developmental junctures) (Flemke & Underwood, 2014), and double betrayal trauma (betrayal trauma coupled with a negative response to CM disclosure to an authority figure) (Wager, 2013).…”
Section: The Complex Linkmentioning
confidence: 99%